2022
DOI: 10.9734/ajmah/2022/v20i1030505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cucumis sativus and Prunus armeniaca Juices on Blood Glucose, Insulin and Electrolytes of Alloxan Induced Diabetic Male Sprague Dawley Rats

Abstract: Aims: To investigate the effects of Cucumis sativus and Prunus armeniaca juices on blood glucose, insulin and electrolytes of alloxan-induced Diabetic male Sprague Dawley rats. Study Design: An experimental study involving a total of eighty (80) male Sprague Dawley rats was used. Place and Duration of Study: Department of Medical Laboratory Science, Rivers State University, Nigeria, between January 2021 and February 2022. Methodology: 80 male Sprague Dawley rats were grouped into eight groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Kaempferol has been reported to lower blood sugar and inhibit alpha-amylase and alpha-glucosidase (two carbohydrate-hydrolyzing enzymes found in the digestive tract) (25). Ibitoye et al showed that kaempferol isolated from cucumber inhibits alpha-amylase and alpha-glucosidase enzymes with anti-diabetic properties and hypoglycemic and antioxidant activities (26). The present study's results were aligned with those of Tamuno-Emine et al, who showed that cucumber juice consumption improved diabetic condition by increasing insulin levels and lowering glucose levels for 35 days in diabetic male Sprague Dawley rats (27).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol has been reported to lower blood sugar and inhibit alpha-amylase and alpha-glucosidase (two carbohydrate-hydrolyzing enzymes found in the digestive tract) (25). Ibitoye et al showed that kaempferol isolated from cucumber inhibits alpha-amylase and alpha-glucosidase enzymes with anti-diabetic properties and hypoglycemic and antioxidant activities (26). The present study's results were aligned with those of Tamuno-Emine et al, who showed that cucumber juice consumption improved diabetic condition by increasing insulin levels and lowering glucose levels for 35 days in diabetic male Sprague Dawley rats (27).…”
Section: Discussionmentioning
confidence: 99%